PROFIL HAMBATAN BELAJAR EPISTIMOLOGIS SISWA KELAS VIII SMP PADA MATERI TEKANAN ZAT CAIR MELALUI TES KEMAMPUAN RESPONDEN - Kartika Mega Lestari; Heni Rusnayati; A. F. C. Wijaya (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Based on the result of a preliminary study, through questionnaire and test showed the learning obstacle experienced by students is still high. Through questionnaires obtained 44.45% of the students and through tests obtained 66.66% of students experiencing learning obstacle on the liquid’s pressure. The purpose of the study to determine the eighth grade student’s epistemological learning obstacle on the liquid’s pressure based on the respondent’s ability test. The method used is descriptive qualitative method uses respondents ability test. Research subject is 39 students in ninth grade in one High School in Bandung. The results of the respondent’s ability test, indicate that as many as 45.72% of students experiencing learning obstacle to the concept of the Law of Archimedes, 36.33% on the concept of the Law of Pascal, 25% on the concept of density, and 17.44% on the concept of hydrostatic pressure. It was concluded that the students experienced the biggest learning obstacle to the concept of Pascal's Law and the Law of Archimedes. So there should be an attempt to minimize these obstacles. Keywords: learning obstacles, respondents ability test, liquid’s pressure.